Adaptasi Perilaku Caring Perawat pada Pasien Covid-19 di Ruang Isolasi - Nova Yustisia; Tuti Anggriani Utama; Titin Aprilatutini (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2020)
Caring is a nursing action based on the desire to understand, help and reduce suffering by taking the best actions for health. Caring behavior must also be given to Covid-19 patients. The research objective was to determine the adaptation of nurses' caring behavior in Covid-19 patients in the RSUD Dr. Isolation room. M. Yunus Bengkulu. This research is a descriptive study with a qualitative approach, involving 10 participants as research subjects. Data collection was carried out through in-depth interviews and observations observing the caring behavior of nurses in providing nursing services to Covid-19 patients. Data analysis techniques include transcripts of interview results, data reduction, analysis, data interpretation and triangulation, which are then concluded. The results of the study were obtained, all the participants had applied aspects of caring, namely caring, responsible, friendly, calm, patient, always ready, motivating, empathetic towards Covid-19 patients and their families, even though there was worry and anxiety in themselves participant. Conclusion, nurses still have caring behavior in providing nursing care and can adapt to apply caring behavior to Covid-19 patients sincerely even though as individuals they have a sense of concern. It is suggested that the spirit of caring should always be turned on in nurses, this requires support from management in improving the physical, mental and spiritual health of nurses so that nurses can provide professional nursing services.Â Keywords: Adaptation, Behavior, Caring